The absolute immunity of the arbitrator: a mistake with historical origins - Martínez-Fraga, Pedro J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This text explores the development of the arbitrator immunity doctrine and its current status under United States common law. In doing so, it examines the manner in which the doctrine has developed in other common law and civil law jurisdictions to provide both a context and a contrast. The text also explores why the United States stands alone in the international community in according arbitrators absolute immunity from civil claims. The text analyzes post-civil war decisions that played a key role in the formation of the doctrine. Finally, it emphasizes the “why” instead of the “what”, and in thus doing posits that methodology and legal reasoning are more important than final conclusions.